Dose-response curves for MRI-detected radiation-induced temporal lobe reactions in patients after proton and carbon ion therapy: Does the same RBE-weighted dose lead to the same biological effect? - Gillmann, Clarissa; Jäkel, Oliver; Karger, Christian (Radiotherapy and oncology, 2018)
Purpose - To derive the dose-response curve for temporal lobe reactions (TLRs) after proton therapy and to compare the resulting relative biological effectiveness (RBE)-weighted tolerance doses based on an RBE of 1.1 with published values for carbon ions, which were calculated by the two versions of the local effect model (LEM I or IV). - Methods and materials - 62 patients treated with protons for skull base tumors were analyzed for TLRs using magnetic resonance imaging. Within the mean follow-up time of 38months, TLRs were observed in six patients. Dose-response curves based on the RBE-weighted maximum dose, excluding the 1cm3-volume with the highest dose, were derived and compared to previously published dose-response curves for carbon ions, which were obtained using LEM I or IV, respectively. - Results - The dose-response curves for protons and LEM I were found to be almost identical while the curve of LEM IV was shifted toward higher doses. The resulting tolerance doses at the 5% effect level were 68.2+2.7-5.6, 68.6+3.0-3.9 and 78.3+3.8-5.0 Gy (RBE), respectively. - Conclusions - The RBE-weighted dose prescription for protons leads to the same RBE-weighted dose-response curve for TLR as the one for LEM I-based carbon ions, while LEM IV predicts clinically significant higher tolerance doses.
Gesehen am 30.04.2019